Review of air disturbance technology for plant frost protection - Hu, Yongguang; Asante, Eric Amoah; Lu, Yongzong; Mahmood, Ashraf; Buttar, Noman Ali; Yuan, Shouqi (International Journal of Agricultural and Biological Engineering, 2018)
Confronted with severe frost damage to plants, methods, technologies and equipment have been developed and applied during the past century. The paper presents a comprehensive review on the most effective and active technology to protect plants from radiation frost based on air disturbance technology. The working principle of the technology was elaborated with frost protection mechanism, structures and applicability of three types of working patterns: conventional wind machines, selective inverted sink and portable vertical blowing. As an automatic mechanized technology, control strategy, applicable occasion and proper parameters are introduced for each type of working pattern. The operation of the technology and equipment depends on plant critical temperature, prevailing climatic conditions, thermal inversions strength, as well as costs. The frost protection performance and effectiveness of conventional horizontal wind machines, selective inverted sinks and helicopters are discussed and compared from the cost-effectiveness and application aspects, and the feasibility of selective inverted sinks is still controversial. Therefore, conventional wind machines are the best choice for plant frost protection and consequently are widely used in temperate and subtropical areas throughout the world. The frost protection application with helicopters is not easy to use during the frost nights with high cost. The paper also provides researchers with some perspectives on improving air disturbance technology and its equipment, and some practice recommendations for growers.Keywords: thermal inversion, plant frost protection, air disturbance technology, wind machine, cost-effectiveness, control technologyDOI: 10.25165/j.ijabe.20181103.3172Citation: Hu Y G, Asante E A, Lu Y Z, Mahmood A, Buttar A N, Yuan S Q. Review of air disturbance technology for plant frost protection. Int J Agric & Biol Eng, 2018; 11(3): 21–28.